2020
DOI: 10.1093/brain/awaa421
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific transcriptomics identifies neddylation as a novel therapeutic target in multiple sclerosis

Abstract: Multiple sclerosis is an autoimmune disease of the CNS in which both genetic and environmental factors are involved. Genome-wide association studies revealed more than 200 risk loci, most of which harbour genes primarily expressed in immune cells. However, whether genetic differences are translated into cell-specific gene expression profiles and to what extent these are altered in patients with multiple sclerosis are still open questions in the field. To assess cell type-specific gene expression in a large coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…We found protein networks and key genes through PPI network analysis. ( ) ( 29 ). Cytoscape software (version 3.8.2) was used to further analyze the network of NRGs.…”
Section: Methodsmentioning
confidence: 99%
“…We found protein networks and key genes through PPI network analysis. ( ) ( 29 ). Cytoscape software (version 3.8.2) was used to further analyze the network of NRGs.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been especially successful for studying diseases of the central nervous system (CNS) due to the incredible complexity and heterogeneity of cell types in the brain. For example, transcriptomics has revealed a novel target, neddylation, that ameliorates the severity of multiple sclerosis in a murine disease model 19 . Transcriptomics has also been applied in Alzheimer's disease (AD) research to expose genetic, cell-type specific regulators of myelination that are perturbed in AD, as well as sex differences in the cellular response to AD 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A further example might be drawn from a study of cell-type specific transcriptomics (80), which identified genes involved in Neddylation as differentially expressed in the lymphocytes (T cells) of MS cases vs. controls. This is striking because Neddylation is evidently also a critical process for EBV and other herpes viruses, so much so that the EBV carries its own deneddylase enzyme amongst its tegument proteins, and antibodies against this viral protein (encoded by gene BPLF1) have recently been identified as a predictor of EBV viral load using an unbiased antibody screening method (80)(81)(82). Pharmacological targeting of viral enzymes is a potential therapeutic strategy, and so may be another fruitful avenue for further exploration.…”
Section: Biological Plausibility For a Causal Associationmentioning
confidence: 99%